EFFECT OF SEASON ON FIRST LACTATION PRODUCTION PERFORMANCE OF MURRAH BUFFALOES - BARMAN, R.S.D.; GREWAL, S.S.; JHA, D.K. (Indian Journal of Animal Production and Management, 2017)
ABSTRACTThe present investigation was conducted on 301 Murrah buffaloes maintained at BuffaloResearch center, Department of Livestock Production and Management, CCS Haryana AgricultureUniversity, Hisar (India) with the main objective to study the Effect of season on first lactationproduction performance of Murrah buffaloes. The overall least-squares means first lactation milkyield, first lactation length, first peak yield and first dry period were obtained as 1991.46 ±26.37 kg, 381.67 ± 3.82 days, 9.58 ±0.99 kg and 188.39 ± 5.05 respectively. The period of calvinghad significant effect on first peak yield and first dry period. Season of calving had significanteffect on first lactation milk yield, first dry period and first lactation length. Each year was dividedin to four season i.e. Summer, Rainy, Autumn and Winter. The least squares means for FLMYindicated that summer (April to June) calvers produced highest milk (2152.17±57.74) yieldfollowed by winter (December to March) calvers but there was no significant difference in summerand winter calvers.Key words : First lactation, Production, Buffaloes, Season